Analysis Of Education Strategy For Community Market Development - Piawan Putra, Azchar Prianka; Mulyanto, Agus Iwan (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2021)
This research is to educate people's market development strategies based on local wisdom in alleviating poverty in Tangerang. The research respondents were officers of the people's market in Tangerang. The results show that the strength in the future is product diversity, local product uniqueness, product quality, merchandise arrangement, flexible pricing, and strategic location. Weaknesses are the availability of a parking area, transaction processing, promotion, cooperation with the tourism industry, orderly zoning, market cleanliness, availability of public facilities, and customer service. Opportunities for the people's market in the future are the level of people's income, the rate of inflation growth, the revitalization of the people's market, security stability, social concern for the people's market, public appreciation, changes in people's tastes, and the adoption of information technology, while the elements that pose a threat are the existence of modern markets. in South Tangerang and its surroundings as competitors and the population growth demographic bonus. Based on the results of the SWOT analysis, the people's market business position is at the base of its development strategy, namely